The Yin and Yang of the oxytocin and stress systems: opposites, yet interdependent and intertwined determinants of lifelong health trajectories - Uvnäs-Moberg, Kerstin; Gross, Mechthild M.; Calleja-Agius, Jean; Turner, Jonathan D. (Frontiers in Endocrinology, 2024)
During parturition and the immediate post-partum period there are two opposite, yet interdependent and intertwined systems that are highly active and play a role in determining lifelong health and behaviour in both the mother and her infant: the stress system and the anti-stress (oxytocin). Before attempting to understand how the environment around birth determines long-term health trajectories it is essential to understand how these two systems operate and how they interact. Here, we discuss together the hormonal and neuronal arms of both the HPA axis and the oxytocinergic systems and how they interact. Although the HPA axis and glucocorticoid stress axis are well studied, the role of oxytocin as an extremely powerful anti-stress hormone deserves more attention. It is clear that these anti-stress effects depend on oxytocinergic nerves emanating from the SON and PVN, and project to multiple sites at which the stress system is regulated. These, include projections to CRH neurons within the PVN, to the anterior pituitary, to areas involved in sympathetic and parasympathetic nervous control, to NA neurons in the LC, and to CRH neurons in the amygdala. In the context of the interaction between the HPA axis and the oxytocin system birth is a particularly interesting period as, for both the mother and the infant, both systems are very strongly activated within the same narrow time window. Data suggest that the HPA axis and the oxytocin system appear to interact in this earlylife period, with effects lasting many years. If mother-child skin-to-skin contact occurs almost immediately postpartum, the effects of the anti-stress (oxytocin) system become more prominent, moderating lifelong health trajectories. There is clear evidence that HPA axis activity during this time is dependent on the balance between the HPA axis and the oxytocin system, the latter being reinforced by specific somatosensory inputs, and this has long-term consequences for stress reactivity.